SOLVING UNBALANCED INTUITIONISTIC FUZZY TRANSPORTATION PROBLEM BY USING THE ROW-COLUMN MAXIMA METHOD - Kokila, A; Deepa, G (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
In this paper, a new method is proposed for finding the optimum solution for an intuitionistic fuzzy transportation problem, entitled the Row-Column Maxima Method [RCMM]. The main goal of this method is to avoid a large number of iterations and to transport the item at the lowest cost from the point of origin to the point of destination. In addition to finding the best solution for an unbalanced transportation problem by turning it into a balanced transportation problem without the need for a fake source or destination, the suggested technique is used to solve both balanced and unbalanced intuitionistic fuzzy transportation problems. All parameters are represented as triangular intuitionistic fuzzy numbers. The proposed method has been illustrated by an example, and the result obtained by the proposed method shows superior performance compared with some existing methods available in the literature. Finally, the proposed technique is demonstrated using a numerical example and a graphical representation of the results. It is the most straightforward approach to resolving real-world transportation problems.